Política de habitação de interesse social: a experiência dos assistentes sociais na região Oeste do Paraná - Heck, Ana Laura Coelho da Silva (2023)
Social Work is a profession inserted in the social and technical division of collective work. As a constitutive part of the transformations in civil and political society, it is present in various socio-occupational spaces, including those perpetuated by the Housing Policy. In the field of social housing, professional practice involves peculiar issues that reflect on the rights of the working class, such as the right to adequate housing and the city. Considering the demand for housing as one of the expressions of the everyday “social issue” that affects social relations established in Brazil, in particular, in the State of Paraná, this dissertation has as its theme: “The issue of housing”. Seeking to deepen this study, we chose as our research object the professional practice of social workers linked to housing policy in the western region of Paraná. The main objective is to understand and analyze the practice of social workers in the development of Social Work in housing in western Paraná. To achieve the general objective, we defined the following as specific objectives: verifying the actions, projects and/or housing programs carried out in the 52 municipalities in the west of the State; identify the group of professional social workers who work in housing policy in western Paraná; highlight the professional practices of social workers in the development of Social Work in housing in the municipalities analyzed. Given the impacts of the implementation of the neoliberal offensive on social policies, with emphasis on the lack of budgetary resources for social housing policy, the question arises: to what extent do government public sphere interventions to meet the demands for housing in the western region of Does Paraná refract in different dimensions in the professional practice of Social Workers? In developing the dissertation, we used bibliographical research and empirical data collection. This is qualitative research intertwined with quantitative dimensions. To carry out data collection, a questionnaire with open and closed questions was applied to social workers who carry out Social Work in Housing in western Paraná. Subsequently, the responses were analyzed using the content analysis methodology. The time frame was delimited between the years 2017 and 2020, considering that it covers the mandate period of the last municipal administration, in which the possibility of meeting the demand for housing in accordance with the respective government proposals and reality was envisaged. local. The results show the development of activities aimed at housing policy by the social worker as a possible way of materializing social rights to housing and the city, based on professional interventions guided by the Ethical-Political Project, with a view to encouraging the exercise of citizenship and improving the population's quality of life.